Gedrukan, Regeng, dan Pemicu Semangat Gerak: Makna Pemakaian Kelinthing dalam Pertunjukan Topeng Ireng - Kiswanto Kiswanto; Bambang Sunarto (Jurnal Kajian Seni, 2020)
The discussion of art is closely related to the issue of symbols and meanings  that has become the foundation on artistic buildings. This also clarifies the existence of art as one of the elements of the embodiment of culture in a society, such as the use of kelinthing in the Topeng Ireng performances. This paper uncovers and explains the forms of artistic expression symbols of the kelinthing and conception of the artist interpret as an element of the Topeng Ireng performances that developed and spread widely in Magelang and surrounding area. Ethnographic approach supported theories related, such as culture, philosophy, and aesthetics into a rationale as outlined by the scientific method in this paper. In this paper shows that the forms of artistic expression symbols of the kelinthing has various meanings associated with intrinsic value (form) and extrinsic value (content). The intrinsic value of kelinthing closely related to dance and music TopengIreng, while the extrinsic value of kelinthing closely related to sound in the show are interpreted regeng. In addition, kelinthing also be interpreted as a stimulus to the spirit of the motion of dancers. AbstrakPembahasan seni terkait erat dengan persoalan simbol dan muatan makna yang telah menjadi pondasi pada bangunan artistiknya. Hal ini sekaligus memperjelas keberadaan seni sebagai salah satu unsur perwujudan kebudayaan dalam suatu masyarakat, seperti pemakaian kelinthing dalam pertunjukan Topeng Ireng. Tulisan ini mengungkap dan menjelaskan bentuk simbol ungkap artistik kelinthing dan konsepsi seniman dalam memaknainya sebagai unsur pertunjukan Topeng Ireng yang berkembang dan tersebar secara luas di wilayah Magelang dan sekitarnya. Pendeketan etnografi dengan didukung teori-teori terkait, seperti kebudayaan, filsafat, dan estetika menjadi landasan pemikiran yang dituangkan dengan metode ilmiah dalam tulisan ini.  Pada tulisan ini menunjukkan bahwa bentuk simbol ungkap artistik kelinthing memiliki makna yang berhubungan dengan nilai intrinsik (bentuk) dan nilai ekstrinsik (isi). Nilai intrinsik kelinthing berkaitan erat dengan gerak tari dan musik Topeng Ireng, sedangkan nilai ekstrinsik kelinthing berkaitan erat dengan bunyinya dalam pertunjukan yang dimaknai regeng. Di samping itu, kelinthing juga dimaknai sebagai pemicu semangat gerak penari.